ICT Innovation, FDI and Economic Growth: Evidence from BRICS - Hammed, Yinka S.; Ademosu, Solomon T. (Journal of Economics and Behavioral Studies, 2023)
We make a comprehensive investigation of ICT innovation, FDI and economic growth nexus for BRICS countries for the periods between 1990 and 2021 using autoregressive distributed lag (ARDL) techniques. We use input-based ICT and non-ICT resources to capture ICT innovations, foreign direct inflows, gross domestic product and quantity of labor for this economic bloc. From our estimation, the following summary can be made. ICT is found to be consistently and significantly contributing to the economic growth rate of BRICS countries. However, with the negative impact of FDI on the growth rate, its interaction with ICT input resources was found to help mitigate the negative impact of FDI on economic growth which by implication suggests that adequate ICT infrastructure complemented with foreign-oriented investment can play a formidable role in increasing the growth process of the economies of BRICS. Also, non-ICT input resources and quantity of labor growth rate were found to be necessary variables worthy of giving appropriate consideration in explaining the growth rate of the economies. The study thus suggests the higher provision of both ICT and non-ICT input resources in the BRICS and a policy to attract able hands from developing countries to turn various resources for economic progress.